نفس انسانی کی علمی و روحانی تسکین کے قرآنی منہاج: Quranic Minhaj of Intellectual and Spiritual Satisfaction of The Human Soul - Shama Naz,; Fizzah Hussain, (Al Manhal Research Journal, 2024)
The Quran is the source of direction and guidance. This is a book of mysteries and wonders. Its wise verses, its arguments and proofs, its rhetoric, its eloquence, its narration of the creation of the universe and the creation of man, scientific facts and prophecies, strange and surprising events, the miracles of the Prophets and its frank manner of speaking awaken the intellect and cconsciousness’ of man. Qur'anic verses and concepts not only give new life to dead hearts and souls but are also means of reforming and α training the human soul. Qur'anic wonders and miracles are a cause of intellectual and spiritual satisfaction of man. They encourage man to act by informing him of his essence and the purpose of life, and he holds the high rank of the commander of the good and the forbidder of the evil. It teaches the ways of life by making him aware of the perfect and flawless system of the universe and makes him entitled to the earthly caliphate.